Hadith #1036 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ﷺ) recited Suratan-Najm (103) at Mecca and prostrated while reciting it and those who were with him did the same except an old man who took a handful of small stones or earth and lifted it to his forehead and said, “This is sufficient for me.” Later on, I saw him killed as a non-believer.
Grade: Sahih

Hadith #1037 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
On Fridays the Prophet (ﷺ) used to recite Alif Lam Mim Tanzil-As-Sajda (in the first rak`a) and Hal ata `alal-insani i.e. Surat ad-Dahr (LXXVI) (in the second rak`a), in the Fajr prayer.
Grade: Sahih

Hadith #1038 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The prostration of Sa`d is not a compulsory one but I saw the Prophet (ﷺ) prostrating while reciting it.
Grade: Sahih

Hadith #1039 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ﷺ) recited Surat-an-Najm (53) and prostrated while reciting it and all the people prostrated and a man amongst the people took a handful of stones or earth and raised it to his face and said, “This is sufficient for me. Later on I saw him killed as a non-believer.”
Grade: Sahih

Hadith #1040 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) I prostrated while reciting An-Najm and with him prostrated the Muslims, the pagans, the jinns, and all human beings.
Grade: Sahih

Hadith #1041 - Sahih al-Bukhari - Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة (Sahih al-Bukhari)
I asked Zaid bin Thabit about prostration on which he said that he had recited An-Najm before the Prophet, yet he (the Prophet) had not performed a prostration.
Grade: Sahih

Hadith #1042 - Sahih al-Bukhari - Zaid bin Asim Mazni (Sahih al-Bukhari)
I recited An-Najm before the Prophet, yet he did not perform a prostration.
Grade: Sahih

Hadith #1043 - Sahih al-Bukhari - Abu Salma al-Himsi Suliaman bin Saleem أبو سلمة الحمصي (Sahih al-Bukhari)
I saw Abu Huraira reciting Idha-Sama’ un-Shaqqat and he prostrated during its recitation. I asked Abu Huraira, “Didn’t I see you prostrating?” Abu Huraira said, “Had I not seen the Prophet (ﷺ) prostrating, I would not have prostrated.”
Grade: Sahih

Hadith #1044 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
When the Prophet (ﷺ) recited a Sura that contained the prostration he would prostrate and we would do the same and some of us (because of the heavy rush) could not find a place for prostration.
Grade: Sahih

Hadith #1045 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
When the Prophet (ﷺ) recited Surat As-Sajda and we were with him, he would prostrate and we also would prostrate with him and some of us (because of the heavy rush) would not find a place (for our foreheads) to prostrate on.
Grade: Sahih

Hadith #1046 - Sahih al-Bukhari - Rabi'a bin 'Uthman bin Rabi'a ربيعة بن عثمان بن ربيعة (Sahih al-Bukhari)
`Umar bin Al-Khattab recited Surat-an-Nahl on a Friday on the pulpit and when he reached the verse of Sajda he got down from the pulpit and prostrated and the people also prostrated. The next Friday `Umar bin Al-Khattab recited the same Sura and when he reached the verse of Sajda he said, “O people! When we recite the verses of Sajda (during the sermon) whoever prostrates does the right thing, yet it is no sin for the one who does not prostrate.” And `Umar did not prostrate (that day). Added
Grade: Sahih

Hadith #1047 - Sahih al-Bukhari - Abu Rafi' (Sahih al-Bukhari)
I offered the `Isha’ prayer behind Abu Huraira and he recited Idhas-Sama’ Un-Shaqqat, and prostrated. I said, “What is this?” Abu Huraira said, “I prostrated behind Abul-Qasim and I will do the same till I meet him.”
Grade: Sahih

Hadith #1048 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Whenever the Prophet (ﷺ) recited the Sura which contained the prostration of recitation he used to prostrate and then, we, too, would prostrate and some of us did not find a place for prostration.
Grade: Sahih